2016
DOI: 10.1016/j.neuroimage.2016.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal frontopolar neural synchronization in group communication: An exploration toward fNIRS hyperscanning of natural interactions

Abstract: Research of interpersonal neural synchronization (INS) using functional near-infrared spectroscopy (fNIRS) hyperscanning is an expanding nascent field. This field still requires the accumulation of findings and establishment of analytic standards. In this study, we therefore intend to extend fNIRS-based INS research in three directions: (1) verifying the enhancement of frontopolar INS by natural and unstructured verbal communication involving more than two individuals; (2) examining timescale dependence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
147
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 183 publications
(154 citation statements)
references
References 86 publications
5
147
0
2
Order By: Relevance
“…The button-press task shed light on the understanding of INS in the prefrontal region but the task setting is close to a laboratory experiment. Extending the previous findings into more real-life oriented social interaction, several studies showed connection between verbal communication and INS (Jiang et al, 2012, 2015; Nozawa et al, 2016). On the other hand, a previous study showed relationship between physical coordination (i.e., non-verbal interaction) and INS (Holper et al, 2012).…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…The button-press task shed light on the understanding of INS in the prefrontal region but the task setting is close to a laboratory experiment. Extending the previous findings into more real-life oriented social interaction, several studies showed connection between verbal communication and INS (Jiang et al, 2012, 2015; Nozawa et al, 2016). On the other hand, a previous study showed relationship between physical coordination (i.e., non-verbal interaction) and INS (Holper et al, 2012).…”
Section: Introductionmentioning
confidence: 57%
“…We used a wireless, portable, and ultra-small NIRS system ( Figure 1A ; Nozawa et al, 2016), which measures changes in the total hemoglobin (tHb) concentration with a light source of single wavelength at 810 nm. The sampling frequency of the device is 10 Hz.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations